Valproate-induced Hyperammonemic Encephalopathy - Hsiao-Feng Chou; Rei-Cheng Yang; Cheng Ying Chen; Yuh-Jyh Jong (Elsevier, 2008)
Valproate-induced hyperammonemic encephalopathy is an unusual but serious complication that can occur in people with normal liver-associated enzyme levels, and despite normal therapeutic doses and serum levels of valproate. Here, we describe an adolescent girl suffering from absence seizures, who complained of progressive dizziness and general malaise several days after restarting valproate. She developed vomiting and decreased consciousness after 3 weeks of valproate use. She had a serum ammonia level five times higher than the upper normal limit, normal liver-associated enzymes, and a supra-therapeutic valproate level. Electroencephalography (EEG) showed continuous generalized slowing. Tandem mass spectrometry analysis revealed carnitine deficiency. Her consciousness improved after emergent hemodialysis. Her ammonia level and EEG also became normal. Possible mechanisms, risk factors and treatments of valproate-induced hyperammonemic encephalopathy are described. Physicians should consider this possibility when consciousness disturbance occurs in patients treated with valproate.